1992
DOI: 10.1099/00221287-138-3-499
|View full text |Cite
|
Sign up to set email alerts
|

Purification of the acidic pectate lyase and nucleotide sequence of the corresponding gene (pelA) of Erwinia chrysanthemi strain 3937

Abstract: The pefA gene from Erwinia chrysmthemi strain 3937, which encodes the acidic pectate lyase, PLa, has been sequenced and characterized. The structural gene consists of a 1179 bp open reading frame encoding a polypeptide of 41 555 Da, which includes an N-terminal signal peptide. The deduced amino acid sequence shows a protein very similar to some PLs already sequenced. Cloning of the pefA gene behind the focZ promoter of the vector pTZ19R allowed overexpression of PLa into a derivative of strain 3937 deleted of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…The lyase of M r 74 kDa required Ca 2+ for maximum activity and yielded a disaccharide containing a A4,5 unsaturated galacturonic acid residue as the major product of polygalacturonic acid digestion. The 'acidic 44-kDa pectate lyase' from Erwinia chrysanthemi also had an alkaline pH optimum (8.2) and activity was optimal in the presence of 5 × 10 -4 mol Ca z÷ [36]. Other monovalent and divalent cations tested did not stimulate enzyme activity.…”
Section: Pectinases Polygalacturonate Lyases and Enteric ' Vi' Antigmentioning
confidence: 94%
“…The lyase of M r 74 kDa required Ca 2+ for maximum activity and yielded a disaccharide containing a A4,5 unsaturated galacturonic acid residue as the major product of polygalacturonic acid digestion. The 'acidic 44-kDa pectate lyase' from Erwinia chrysanthemi also had an alkaline pH optimum (8.2) and activity was optimal in the presence of 5 × 10 -4 mol Ca z÷ [36]. Other monovalent and divalent cations tested did not stimulate enzyme activity.…”
Section: Pectinases Polygalacturonate Lyases and Enteric ' Vi' Antigmentioning
confidence: 94%
“…PEL sequences of a recombinant protein have also been reported from banana (Pua et al, 2001;Maŕin-Rodŕiguez et al, 2003), but the enzyme activity has only been recently demonstrated (Maŕin-Rodŕiguez et al, 2003;Payasi and Sanwal, 2003). PELs have been purified and characterized from several microbial sources (Favey et al, 1992;Bruhlmann, 1995;Liao et al, 1997;Kobayashi et al, 1999;Kluskens et al, 2003), but studies from plant sources are lacking (Maŕin-Rodŕiguez et al, 2002). To the best of our knowledge no report exists on purification of PEL to homogeneity from plant sources.…”
Section: Introductionmentioning
confidence: 92%
“…The pI of a protein is important because it represents the point at which the protein is least soluble, and therefore unstable (Shaw et al, 2001). Thus, the low pI value of PelA may contribute to its poor cellwall macerating efficiency, due the acidic pH of plant tissues (Favey et al, 1992;Tardy et al, 1997). Despite its poor maceration ability, PelA is essential for the full pathogenicity of D. dadantii (Boccara et al, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…The fact that phytopathogenic organisms are often encountered in soil raises the possibility that the acidic PLs may have physiological functions that are important for survival outside the plant tissue (Favey et al, 1992). MEME revealed seven conserved motifs in the 22 evaluated sequences.…”
Section: Discussionmentioning
confidence: 99%